Towards a New Tax-Transfer System in Canada: An Analysis of the Changes Proposed in the White Papers on Income Security, Unemployment Insurance and Taxation - David A. Dodge; John H. Sargent (Queen's University, Department of Economics, 1971)
Recent issues of the Canadian Tax Journal have included analyses of each of the federal governmment's three major programmes for reform of Canada's tax-transfer payment system. In this article, we pay particular attention to tax-like effects of the programmes and to issues that were important in the tax reform debate: questions of the impact on incentives for individuals to work, save, etc. In a number of instances, we examine the combined effects of the proposals from these points of view. Finally, we discuss the 'negative income tax' method as an alternative to some of the major components of the unemployment insurance and income security reforms.
Keywords: 330